2018
DOI: 10.1021/acs.analchem.8b00242
|View full text |Cite
|
Sign up to set email alerts
|

Direct Analysis in Real Time Mass Spectrometry for Characterization of Large Saccharides

Abstract: Polysaccharide characterization posts the most difficult challenge to available analytical technologies compared to other types of biomolecules. Plant polysaccharides are reported to have numerous medicinal values, but their effect can be different based on the types of plants, and even regions of productions and conditions of cultivation. However, the molecular basis of the differences of these polysaccharides is largely unknown. In this study, direct analysis in real time mass spectrometry (DART-MS) was used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…DART ionization source is capable of breaking down large and intact polysaccharides into small fragments instantaneously. 31 In this work, the factors affecting the DART-MS analysis of polysaccharides were systematically studied. The intensities of the main fragments (peak areas of DART-MS extracted ion chromatogram) from different F I G U R E 1 Overall fingerprint protocol for herbal polysaccharides includes 40-60 s mechanochemical extraction (MCE), removal of impurities using ultrafiltration membrane with molecular weight cut-off (MWCO) of 3 kDa, and direct analysis in real-time mass spectrometry characterization.…”
Section: Dart-ms Analysis Of Polysaccharidesmentioning
confidence: 99%
See 1 more Smart Citation
“…DART ionization source is capable of breaking down large and intact polysaccharides into small fragments instantaneously. 31 In this work, the factors affecting the DART-MS analysis of polysaccharides were systematically studied. The intensities of the main fragments (peak areas of DART-MS extracted ion chromatogram) from different F I G U R E 1 Overall fingerprint protocol for herbal polysaccharides includes 40-60 s mechanochemical extraction (MCE), removal of impurities using ultrafiltration membrane with molecular weight cut-off (MWCO) of 3 kDa, and direct analysis in real-time mass spectrometry characterization.…”
Section: Dart-ms Analysis Of Polysaccharidesmentioning
confidence: 99%
“…29,30 We reported earlier the phenomenon that DART ion source is capable of breaking down intact polysaccharides instantaneously into small fragments. 31 This work presents a rapid, simple, and high throughput fingerprint protocol for herbal polysaccharides, which involves efficient mechanochemical extraction (MCE) followed by direct DART-MS characterization. The whole procedure can be accomplished in a few of minutes from raw materials.…”
Section: Introductionmentioning
confidence: 99%
“…However, DART MS obviates a separate hydrolysis step since polysaccharides undergo thermal decomposition during DART ionization, generating characteristic pro les consisting of smaller fragments (m/z <350) in the ion source. 20) Many of the signals correspond to mono-and oligosaccharides. is feature was e ectively used to characterize the origin of traditional Chinese herbal medicines (TCHM).…”
Section: Chemotaxonomy By Lipids Alkaloids and Saccharidesmentioning
confidence: 99%
“…Ma et al showed that six di erent herbal TCHMs could be distinguished on the basis of plant polysaccharide decomposition products. 20) Individual species also could be identi ed when mixed with one or two other species, indicating distinct polysaccharide compositions for each herb. Moreover, the same TCHM from di erent production regions also could be separated on the basis of DART ionization-produced polysaccharide fragments.…”
Section: Chemotaxonomy By Lipids Alkaloids and Saccharidesmentioning
confidence: 99%
“…However, in DART work dealing with saccharides or glycosides, the emphasis was not on achieving accurate mass or exploiting these cluster ions for mass calibration. [25][26][27] The combination of DART with the high resolving power and mass accuracy of Fourier transform ion cyclotron resonance (FT-ICR) [13][14][15]28,29 and Orbitrap analyzers [30][31][32] is particularly effective in compound identification. Highest mass accuracy is generally achieved by combining the procedure of instrument tuning and mass calibration in a dedicated method file.…”
Section: Introductionmentioning
confidence: 99%